Good Night, Baddies - Underwood, Deborah; Kangas, Juli (New York : Beach Lane Books, 2016)
"After a full day of evil schemes, fairy tale baddies return home to spend time with their friends and get ready for bed in this cozy bedtime book"--
Keywords: Bedtime -- Juvenile fiction; Villains -- Juvenile fiction; Fairy tales -- Juvenile fiction; Bedtime -- Fiction; Villains -- Fiction; Fairy tales -- Fiction; JUVENILE FICTION / Bedtime & Dreams; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Monsters